Rasionalitas Pengobatan Diabetes Melitus Tipe II - Aquila Graham Gibraltar Sihombing (Yayasan Pendidikan Medika Indonesia, 2022)
Type II diabetes mellitus is a disease that has high morbidity and mortality rates. Therapy for this disease is comprehensive. The rationality of treatment supports the successful management of diabetes mellitus. The purpose of this paper is to determine the rationality of the treatment of type II diabetes mellitus. The method used is literature research by looking for drugs, rationality, type II diabetes mellitus, management, management at Google Scholar and Pubmed. Searching the literature from both national and international journals then summarizes the discussion topics and compares the results presented in the articles. From a review of the existing literature, the rationale for treatment includes the correct diagnosis, the right indication, the right dose, the right route of administration, the right time interval for administration, and the right patient.